The Impact of Early Childhood Teacher’s Perception on the Development of Creative Curriculum: A Mixed Approach - Fatima AlMohsen (Journal of Studies in Education, 2024)
The current study focuses on investigating the impact of early childhood teacher’s perception on the development of creative curriculum. Mixed approach was taken to analyse the findings of the study. For the qualitative study, past papers and scholarly researches have been taken to touch the deeper roots of the topic. Moreover, for the quantitative approach, regression analysis was conducted to statistically test the significance of the variables on the study variable. The main objective of the study was to examine the views of the early childhood teachers in creating the curriculum for the students. To collect the responses, semi-structured interviews were undertaken to know the responses of the teacher that were later encoded to perform the regression analysis. The findings showed that, teacher’s role and perception has a significant impact on creative curriculum development as teachers are the main actors engaged in student teacher learning and experiment multiple methods in enhancing the learning experience of the students. Finally, it is recommended to conduct the longitudinal study in the future research to have the more detailed analysis of the study.